Early histological and functional study of radial optic neurotomy outcomes in normal rat eyes - Belforte, Nicolás Adalberto (2011)
BACKGROUND: Radial optic neurotomy (RON) has been proposed as a treatment for central retinal vein occlusion. However, it is still under debate whether RON would be an adequate treatment or a dangerous procedure, and persuasive animal studies are lacking. The aim of this study was to analyze the early histologic and functional outcomes of RON in normal rat eyes. METHODS: Radial optic neurotomy was performed by cutting into the optic nerve edge at the nasal hemisphere, while the contralateral eye underwent a sham procedure. The retinal function was assessed by scotopic electroretinography, and the visual pathway was assessed by flash visual evoked potentials. Intraocular pressure was assessed with a tonometer, the pupillary light reflex was measured after exposing eyes to a 30-second light flash, whereas the optic nerve head structure was examined by histologic analysis. RESULTS: In normal rat eyes, RON provoked minor histologic alterations at the optic nerve head level and a transient decrease in the electroretinography. No changes in visual evoked potentials, intraocular pressure, and pupillary light reflex were observed in rat eyes submitted to RON. CONCLUSION: To our knowledge, this is the first study describing the early histopathologic and functional consequences of RON in normal rat eyes.